On the 30th anniversary of higher nursing education at Kazan State Medical University — on bachelor's degree program in nursing - O. N. Morozova; O. R. Radchenko; E. A. Tafeeva; A. V. Shulaev; L. T. Gubaeva (Кардиоваскулярная терапия и профилактика, 2025)
The article presents an overview of publications on higher nursing education in Russia and an analysis of the experience of Kazan State Medical University. In addition, we assessed demand for the faculty and satisfaction with the training and learning process according to student survey data.The analysis of publications showed that higher nursing education was dictated by the healthcare system reform, the integration of Russia into the European educational and scientific space. There is a high competition at Kazan State Medical University over the past 10 years (7,51±3,3 people per place). The increase in the number of full-time students rationaled the opening of a part-time department. Survey results showed that part-time students with experience in health facilities approach study more consciously than students after school.A summary of experience on training medical personnel in the higher nursing education program and an analysis of students' opinions on the educational process at Kazan State Medical University made it possible to propose the main ways to improve the education.